Enhanced n‐butanol permselective vapor permeation by incorporating ZIF‐8 into a polydimethylsiloxane composite membrane: Effect of filler loading contents. Issue 12 (4th April 2022) - Su, Xing; Zheng, Tucai; Zhu, Youliang; Tao, Xiaohong; Yu, Kuangli; Zhao, Zhiqing; Wu, Zhenghong; Lu, Jiale; Gao, Chuanhua; Zhao, Dian
Abstract: Fabricating high‐performance mixed matrix composite membranes (MMMs) based on the integration of metal‐organic frameworks (MOFs) and hydrophobic polymer matrix are highly sought for the industrial development of vapor permeation (VP) technology. In this work, ZIF‐8@polydimethylsiloxane/polyvinylidene fluoride (ZIF‐8@PDMS/PVDF) MMMs with various ZIF‐8 nanofiller loading contents were prepared via a simple "prime" blending method. The dispersion and agglomeration of ZIF‐8 nanoparticles on both surface and cross‐section of these membranes were characterized by scanning electron microscopy (SEM) and energy‐dispersive X‐ray spectroscopy (EDS), respectively. The hydrophobicity of as‐obtained MMMs was investigated by water contact angle and swelling degree tests. Furthermore, VP experiments were carried out to evaluate the perm‐selection performance of the ZIF‐8@PDMS/PVDF MMMs for the butanol/water mixture separation. Compared to the conventional PDMS membrane, the separation factor and total flux of MMM with ZIF‐8 loading content of 20 wt% increased by 70 % and 23 %, respectively. The mechanism of mass transfer of butanol and water molecules inside the MMMs was also discussed. Abstract :